Infographics as an alternative da’wah medium during Covid-19 crisis - Anwar Ahmad Fauzi; Norazmi Anas; Shahrel Nizar Baharom; Zuriani Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2022)
Infographics are visual representations of complex information or data created by combining elements such as symbols, graphics, shapes, pictures, texts and illustrations to present information in a simple, concise and easy to understand manner that piques the reader’s or viewer’s interest. Based on these criteria, infographics are deemed highly suitable for use as a medium for contemporary da’wah in an age of media centralization, particularly among the young. The current COVID-19 pandemic has severely harmed traditional preaching and learning through lectures and talks in mosques and suraus, particularly in our country, Malaysia. This is due to the strict enforcement of the Movement Control Order (MCO), which limits movement and mass gathering with strict Standard Operating Procedures (SOP) and suspends all religious activities. In order to overcome obstacles to preaching, we must creatively diversify the method of da’wah based on the concept of murunah (flexibility), which is the foundation of Islamic tasawwur in implementing Shariah. Thus, the objectives of this study are to (i) explain the idea of ICT-based da’wah, (ii) analyse the concept of infographics and multimedia in da’wah, and (iii) summarise the community’s perspective of infographics as an interactive da’wah medium. This study employed exploratory sequential mixed methods, beginning with a qualitative literature review using content analysis, followed by quantitative perception questionnaire, analyzed using descriptive analysis. The findings of the study finds that an average of 91.3% of the respondents agreed that infographics represent a significantly suitable form of visual information through social media for most people, especially during the COVID-19 crisis for the continuity of Islamic da’wah.